Correction: The impact of doping rates on the morphologies of silver and gold nanowires grown in helium nanodroplets. Issue 4 (5th January 2016) - Volk, Alexander; Thaler, Philipp; Knez, Daniel; Hauser, Andreas W.; Steurer, Johannes; Grogger, Werner; Hofer, Ferdinand; Ernst, Wolfgang E.
Abstract : Correction for 'The impact of doping rates on the morphologies of silver and gold nanowires grown in helium nanodroplets' by Alexander Volk et al., Phys. Chem. Chem. Phys., 2016, DOI: ; Web:10.1039/c5cp06248a .